Resilience Theory: Adaptation and Transformation of the Film Community due to the Pandemic - Erris RF Wijaya; Andre N Rahmanto; Albert MI Naini (PT FORMOSA CENDEKIA GLOBAL, 2022)
The Covid-19 pandemic had forced cinemas to close and the film industry to dim. Cinema closures are a serious issue for moviegoers and the film community. This research tries to find out how the film community is surviving amidst a pandemic. Qualitative methods are used to develop the research. Data collection is done through interviews. The analysis was carried out by adopting resilience communication theory to find out how the film community deals with pandemic situations. The results of the study show that 1) moviegoers adopt subscription video services (over-the-top) as an alternative to cinemas; 2) internet-based chat rooms and online meetings are alternatives to physical meetings; 3) the new normal period does not necessarily erase the habits that have been built during the pandemic; and 4) a pandemic is not always a hindrance, but also triggers the productivity and creativity of moviegoers